Factors affecting adoption and intensity of conservation agriculture techniques applied by smallholders in Masvingo district, Zimbabwe. Issue 4 (2nd October 2017) - Kunzekweguta, Machiweyi; Rich, Karl M.; Lyne, Michael C.
ABSTRACT: This study investigates factors influencing both the use of conservation agriculture (CA) and the intensity of its uptake amongst 237 smallholders sampled in the Masvingo district of Zimbabwe. The intensity of uptake was measured using an index that accounted for the number of CA components used, their relative importance, and the rate and extent of their application. Previous studies ignore some or all of these important aspects of uptake. The determinants of use and intensity were identified using a double hurdle model. Although most smallholders applied the reduced tillage or crop rotation components of CA, few combined these practices with mulching. Farm size and experience with CA technology impacted positively on the current use of CA, while distance from town (market) and ownership of an ox-drawn plough reduced the intensity of its uptake. Sensitivity analysis showed that these results change when partial measures of CA uptake are used, emphasising the importance of establishing a comprehensive measure of intensity. Policy implications include a need for institutional change to improve smallholder access to cropland, more participatory approaches to agricultural extension, and more convenient access to farm inputs.